Characterizing whole-body and regional adipose tissue distribution in older and younger adults - Rosati, Katherine (University of Waterloo, 2025)
Background: Aging is associated with a loss of skeletal muscle as well as a gain in whole body adipose tissue and increased fatty infiltration into muscle. Despite the known poor health outcomes associated with increased adiposity, there are sparce data regarding increased regional adipose tissue with age. Ultrasound has emerged as an accurate and precise body composition modality that can predict muscle and adipose tissue features, such as thickness and echointensity, and may circumvent many of the limitations associated with other body composition modalities. Thus, I sought to investigate adipose tissue characteristics across 8 anatomical landmarks characterized by weight-bearing and non-weight bearing regions of the body in a heterogenous population. Objectives: The primary objective of this thesis was to measure adipose tissue thickness at the anterior upper leg (AUL) and compare this site with 7 other anatomical landmarks in older adults using ultrasound: anterior upper arm (AUA), posterior upper arm (PUA), posterior upper thigh (PUL), anterior forearm (AF), abdomen (ABD), posterior lower leg (PLL), and anterior lower leg (ALL). The secondary objectives were to: 1) measure and compare adipose tissue echointensity at the AUL with the 7 other anatomical landmarks in older adults, 2) evaluate if sex and age are associated with adipose tissue thickness and 3) if sex, age and adipose tissue thickness are associated with adipose tissue echointensity. The tertiary objective was to evaluate the relationship between ultrasound-based adipose tissue thickness and echointensity when controlling for fat mass index (kg/m2). Methods: Healthy adults (>18 years old) were recruited for whole-body DXA scans and 8 regional landmark ultrasound scans. Anatomical landmarks were based on a 9-site protocol; from this iii protocol, 8 regional landmarks at the ABD, AUA, AF, PUA, PLL, ALL, AUL and PUL were used for the study. Whole-body DXA was used to determine physical characteristics including body fat percentage and fat mass index. Fat mass index (FMI) was calculated by adding all regional fat mass segments and dividing by height squared (kg/m2). Results: We performed a secondary analysis with 128 participants (42.9% females), including older adults (n=73, 74.1 +7.0 years of age) and younger adults (n=55, 27.1+6.9 years of age) . Adipose tissue thickness at the AUL was significantly lower compared to the ABD by 1.34 + 1.0cm, and was greater than the AF, AUA and ALL by 0.54 + 0.69cm, 0.39 + 0.59cm, 0.71+ 0.71cm respectively in older adults. Adipose tissue echointensity at the AUL was significantly greater compared to the ABD, AUA, PUA, PUL by 24.9+17.7a.u., 10.4+14.9a.u., 14.8+15.9a.u., 3.8+15.4a.u., respectively in older adults. Significant differences were observed across all nonweight bearing landmarks between older and younger adults. Regression analyses revealed sex and age non-uniformly influence adipose tissue thickness and echointensity across all 8 landmarks, even when controlling for FMI. Conclusions: This thesis demonstrated that older adults experience a non-uniform body composition distribution, specifically between weight bearing vs non-weight bearing regions. When compared to 7 regional landmarks, the AUL site had distinct adipose tissue thickness and adipose tissue echointensity in older adults, which may be attributed to age and sex, as shown by the independent and interaction effect of age and sex across all landmarks. Overall, this thesis determines the importance of investigating age-related adipose tissue distribution and applying non-invasive tools like ultrasound in the understanding of adipose tissue in diverse populations
Keywords: body composition; ultrasound; aging; adipose tissue; echointensity